Uncertainty about trade policy uncertainty - Gianluca Benigno; Jan J. J. Groen (Federal Reserve Bank of New York, 2020)
We revisit in this note the macroeconomic impact of the recent rise in trade policy uncertainty. As in the literature, we do find that high trade policy uncertainty can adversely impact domestic and foreign economic activity. In addition, we identify an alternative business sentiment channel that is separate and distinct from the impact of trade policy uncertainty, which provides a complementary explanation of the recent developments in the U.S. and global economic activities. This sentiment channel also implies that subsiding trade policy uncertainty does not necessarily result in a recovery of the manufacturing sector and investment spending as long as business sentiment remains negative.
Keywords: C11; C22; 330; uncertainty; trade policy; business sentiment